The genus Austrophilopterus Ewing (Phthiraptera: Philopteridae) from toucans, toucanets, and araçaris (Piciformes: Ramphastidae) - Price, Roger D.; Weckstein, Jason D. (Zootaxa, 2005)
Examination of material representing the 24 previously named species and subspecies of Austrophilopterus resulted in recognition of only 6 of these as valid species and 18 as synonymies, including a previously established junior synonym and 17 new synonymies. These 6 species are redescribed and illustrated. One new species, A. thysi, is described from the type host Selenidera gouldii (Natterer).